Soy protein isolate-polyguluronate nanoparticles loaded with resveratrol for effective treatment of colitis. (1st June 2023) - Li, Wenhao; Bi, Decheng; Yi, Jiang; Yao, Lijun; Cao, Jue; Yang, Peng; Li, Meiting; Wu, Yan; Xu, Hong; Hu, Zhangli; Xu, Xu
Highlights: A novel glycoprotein of soy protein isolate-polyguluronate was successfully prepared. SPI-PG-RES had better pH stability, storage stability and bioavailability. SPI-PG-RES had better antioxidant activity and prevention of colitis than free RES. Abstract: Polyguluronate (PG) is an acidic homopolymer of α-(1, 4)-l -guluronate separated from alginate. In this study, PG was first grafted with soy protein isolate (SPI) through the Maillard reaction to obtain a new glycoprotein (SPI-PG). Then, this novel glycoprotein was used to prepare nanoparticles to encapsulate the resveratrol (RES). Our results showed that SPI-PG-RES had better pH stability, storage stability and ionic stability than SPI-RES. In vitro digestion experiments showed that the RES bioavailability of SPI-PG-RES was much higher than that of free RES and SPI-RES. Furthermore, the in vitro antioxidant capacity of SPI-PG-RES was much stronger than that of free RES and SPI-RES. In addition, SPI-PG-RES was more effective in preventing the symptoms of DSS-induced colitis than RES and SPI-RES. These results suggested that the protein nanoparticles prepared using SPI-PG were a stable and effective hydrophobic polyphenol carrier and could be applied to food-grade components in functional foods and nutritional supplements.